Studi Efek Samping Obat Antituberkulosis (OAT) Pada Pasien TB Paru - Nur Rasdianah; Madania Madania; Teti Sutriati Tuloli; Widy Susanti Abdulkadir; Hidayat Ahmad; Tri Bella Angraini Suwandi (State University of Gorontalo, 2022)
Tuberculosis is a contagious infection caused by Mycobacterium tuberculosis. Tuberculosis can be cured if the patients receive maximum treatment, but most patients feel uncomfortable with the side effects of the antituberculosis drugs consumed so patients experience drop out during the treatment period. This research aims to evaluate the side effects of antituberculosis drugs and their management in patients with pulmonary TB at RSUD Dr. MM Dunda Limboto after receiving antituberculosis drugs category 1. This is observational descriptive research using the prospective method for 1 month with 45 patients as the sample. The finding shows that the most common side effects suffered by pulmonary TB patients after taking antituberculosis drugs category 1 are reddish urine by 31 patients (69%), malaise by 21 patients (47%), dizziness by 17 patients (38%), and nausea by 13 patients (29%). The side effect that occurs the least is an increase in the value of SGOT/SGPT by 2 patients (4%). The conclusion is that the most common side effects experienced are reddish urine, malaise, dizziness, and nausea. Handling of side effects of antituberculosis drugs is done by giving symptomatic drugs such as antiemetics, analgesics, antipyretics and vitamin B6 to patients who experience side effects.